Analisis Permintaan Dan Penawaran Tenaga Kerja Pada Sektor Pertanian Di Provinsi Aceh - Agustina Arida; Zakiah Zakiah; Julaini Julaini (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. Labor is one of the most important production factors in supporting economic growth in addition to the factors of production land, capital and management / skill. Aceh is one of province in Indonesia, which has a larger population and some people made their living in the agricultural sector. The agricultural sector in Aceh were able to absorb labor is relatively larger than the other sectors, the contribution of the agricultural sector in Aceh not only in employment but also to PDRB.This study aimed to analyze the factors that affect the demand and supply of labor in the agricultural sector in the province of Aceh. On the demand equation factors analyzed are land, labor, and agricultural investment. On the supply equation factors analyzed were quality of population, wage labor in agriculture and unemployment in rural. The results of labor demand analysis, show that the variable land and agricultural sector investment gave positive effect and significance on labor demand, and labor variable agricultural sector gave a negative effect but no significant on labor demand. The results of labor supply analysis show that variable labor in agriculture and unemployment in rural gave positive effect and a significant influence on labor supply, while a quality of residents variable gave a positive influence but not significant on labor supply.